Penatalaksanaan Giant Unilateral Non-Hodgkin Primary Breast Lymphoma Mimicking Phyllodes Tumor pada Pasien di Rumah Sakit : Laporan Kasus - Naela Himayati Afifah; Lina Choridah; Didik Setyo Heriyanto (Jurnal Imejing Diagnostik (JImeD), 2026)
Background: Primary breast lymphoma (PBL) is a rare malignancy, accounting for approximately 0.4% of all breast neoplasms. Clinically and radiologically, PBL may mimic other breast tumors, particularly breast carcinoma or phyllodes tumors. This study aims to report a rare case of giant unilateral primary breast lymphoma that initially mimicked a phyllodes tumour on imaging examination. Methods: This study was conducted as a case report of a 53-year-old woman presenting with a rapidly enlarging breast mass. Clinical examination and breast ultrasonography were performed to evaluate the characteristics of the lesion. Ultrasound imaging assessed the size, internal structure, and associated lymph node involvement. A definitive diagnosis was established through histopathological and immunohistochemical examinations. The diagnosis of PBL was confirmed based on established criteria, including the absence of prior extramammary lymphoma and no evidence of systemic disease. Results: The patient presented with a large, rapidly growing, and painful mass in the right breast. Ultrasonography demonstrated a diffuse, inhomogeneous solid mass without spiculations, architectural distortion, or microcalcifications, and no evidence of axillary lymph node enlargement. Based on these findings, the lesion was initially suspected to be a phyllodes tumour. However, histopathological and immunohistochemical analyses confirmed B-cell Non-Hodgkin lymphoma. The tumor exhibited several imaging features similar to phyllodes tumour, including giant size, unilateral presentation, and a diffuse solid structure without spiculation, calcification, or axillary lymphadenopathy. Nevertheless, hypervascularity and the absence of a cleft cyst suggested lymphoma. Conclusions: Primary breast lymphoma should be considered in the differential diagnosis of large breast masses, particularly when imaging findings show hypervascular lesions without spiculation, calcification, or axillary lymph node involvement. Accurate diagnosis requires histopathological confirmation to differentiate PBL from other breast tumors such as phyllodes tumour and breast carcinoma.